A European approach to clinical investigator training - Boeynaems, Jean-Marie; Canivet, Cindy; Chan, Anthony; Clark, Mary Jane; Cornu, Catherine; Daemen, Esther; Demotes, Jacques; De Nys, Katelijne; Hirst, Barry; Hundt, Ferdinand; Kassai, Behrouz; Kerpel-Fronius, Sandor -.; et al. (Frontiers in Pharmacology, 2013)
A better education and training of clinical investigators and their teams is one of the factors that could foster the development of clinical research in Europe, a key objective of the Innovative Medicines Initiative (IMI). PharmaTrain (an IMI programme on training in medicines development) and ECRIN (European Clinical Research Infrastructures Network) have joined forces to address this issue. An advisory group composed of representatives of universities, pharmaceutical companies and other organisations met four times between June 2011 and July 2012. This resulted in a position paper proposing a strategy to improve and harmonize clinical investigator training in Europe, and including a detailed syllabus and list of learning outcomes. Major recommendations are the establishment of minimal and mutually recognized certification requirement for investigators throughout the EU and the creation of a European platform to provide a suitable course and examination infrastructure.